Análise do ponto de congelamento do leite por método de precisão e por espectroscopia com Transformada de Fourier no Infravermelho (FTIR) - Rommel Furst Brito (2019)
A total of 480 milk samples were analyzed in four repetitions with four preservative treatments (no preservative, Bronopol, Bronolat and Brononata), three storage times at temperatures up to 4 °C (24, 48 and 72 hours after reception), five different water additions (0.0, 2.5, 5.0, 7.5 and 10.0%) and two analytical instruments (electronic cryoscope and FTIR). The objective of this study was to evaluate the effect of these parameters in the determination of the freezing point by the reference method and by Fourier transform infrared spectroscopy, thus determining the best analytical conditions and establishing a mathematical equation for electronic determination by FTIR spectroscopy. Bronolat was the best preservative and Brononata was the worst and it is not recommended to analyze freezing point by FTIR. The storage time of the samples did not interfere in the analytical determinations by the precision method and by FTIR. Keywords: freezing point, raw milk, Bronopol, Bronolat, Brononata, electronic cryoscope, FTIR, storage time